(untitled) (Journal of Computational Mathematics, 2000)
In this paper, the Crank-Nicholson+component-consistent pressure correction method for the numerical solution of the unsteady incompressible Navier-Stokes equation of [1] on the rectangular half-staggered mesh has been extended to the curvilinear half-staggered mesh. The discrete projection, both for the projection step in the solution procedure and for the related differential-algebraic equations, has been carefully studied and verified. It is proved that the proposed method is also unconditionally (in Δt) nonlinearly stable on the curvilinear mesh, provided the mesh is not too skewed. It is seen that for problems with an out flow boundary, the half-staggered mesh is especially advantageous. Results of preliminary numerical experiments support these claims.